Non-clinical performance and acceptability of a small portable respiratory stimulator device for basic neonatal resuscitation - Delgado, Carlos A. (2019)
Introduction: Neonatal resuscitation demands equipment for respiratory support not always available in rural areas. Innovative devices are required, and rapid prototyping allows to generate them using three-dimensional (3D) designs and printers. Objective: To evaluate the non-clinical performance and the acceptability by health personnel of a neonatal respiratory device produced by rapid prototyping. Methods: Observational study, descriptive, of proof of concept developed in two steps. Step 1: Manufacture of the device with rapid prototyping in three-dimensional (3D) scanners and printers. Step 2: Demonstration of the invention during training programs in neonatal resuscitation for health personnel in three regions of Peru (Tarapoto, Huánuco and Ayacucho). In both steps, we evaluated the performance of the device connected to a gas flow analyser. A survey was administered to the health workers of Tarapoto and Ayacucho to know their acceptability. Results: The developed prototype is T-shaped with two side bellows that, when pressed with one hand, project air through the centre towards a facial adapter. The use of the prototype in the laboratory generated an average air flow of 4.8 Lt /min (SD ± 1.7) and an average pressure of 5.9 cmH2O (SD ± 1.4). This device was considered to be “very simple to use” in an acceptability survey involving 39 nurses and 11 doctors in remote areas of the capital of Peru. Conclusions: The evaluated prototype is acceptable by the staff and has a performance capable of generating spontaneous breathing at birth.